Optimalisasi Pengasuhan melalui Psikoedukasi Manajemen Stres untuk Mencegah Stunting Anak Usia Dini di Kantor Kecamatan Tambaksari: Optimising Parenting through Stress Management Psychoeducation to Prevent Early Childhood Stunting in Tambaksari District Office - Kusumawati, Elza; Ramadhani, Fitriani Rahma; Apriawan, Aris Maulana Vicky; Alfarizi, Muchammad Fitroh; Samudra, Rahmad Bintang; Hartanti, Lutfiana Nabilah; Pratama, Stefanus Putra; Rachmawati, Anissa Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Stunting in early childhood in Surabaya City, especially in Tambaksari District, is still a special concern even though it has decreased yearly. The Stress Management Psychoeducation Activity for Parents and Caregivers aims to increase the understanding and skills of parents and caregivers in managing stress which is expected to optimize parenting to prevent stunting. Psychoeducation is conducted through interactive seminars with the AAABC (Accept, Alter, Avoid, Building, and Change) method by delivering material on stress recognition, causative factors, and stress management techniques, such as breathing relaxation and meditation. This activity involved 42 participants previously members of the Sekolah Orang Tua Hebat program. The pre-test and post-test results showed a significant improvement based on the paired sample t-test results with a significant value of 0.000 (<0.05) which proves that this stress management psychoeducation is effective and contributes importantly to efforts to create better parenting and support Surabaya's vision of becoming a zero stunting city.